VRRP : Increasing Reliability and Failover with the Virtual Router Redundance Protocol - Srikanth, Ayikudy; Onart, Adnan (Addison-Wesley Professional, 2002)
"A detailed and clearly written book that is an invaluable resource to all VRRP users and implementers." --Scott Bradner, Senior Technical Consultant, Harvard University By employing the Virtual Router Redundancy Protocol (VRRP), administrators can ensure that their networks remain up and running, thereby eliminating expensive downtime. Using VRRP to avoid network outages is essential to building accessible, robust networks, and central to the implementation of successful disaster recovery models. Written by experts who contributed to the design of the VRRP protocol and participated actively in its deployment, VRRP: Increasing Reliability and Failover with the Virtual Router Redundancy Protocol is your best introduction to this powerful high-availability tool. VRRP examines the general characteristics of the protocol and its usage. The emphasis is on translating the protocol specification into a tutorial form ideal for day-to-day users of VRRP. In addition to introducing the technology, this book provides an in-depth analysis, featuring extensive material on configuring, managing, and troubleshooting VRRP. Precursors to this protocol, such as Cisco's HSRP and DEC's IPSTP, are also discussed. Various vendor-specific extensions to VRRP--and their use in solving specific high-availability problems not addressed by VRRP--are also examined. Network administrators and managers, protocol implementers, practicing professionals, researchers, and students exploring the area of high availability will gain a solid understanding of the core concepts of reliability and redundancy based on VRRP, as well as the particulars of the VRRP protocol and how to implement it. The appendixes provide the necessary background for networking and TCP/IP, the full text of VRRP MIB, a study of actual VRRP implementations and an analysis of public-domain software available for VRRP over Linux, an overview of the VRRP state machine using SDL flowcharts and UML diagrams, and an analysis of the protocol through formal logic. 0201715007B09052002.